Massive earthquake swarm driven by magmatic intrusion at the Bransfield Strait, Antarctica - Cesca, Simone (Dr.); Sugan, Monica; Rudzinski, Lukasz; Vajedian, Sanaz; Niemz, Peter; Plank, Simon; Petersen, Gesa; Deng, Zhiguo; Rivalta, Eleonora; Vuan, Alessandro; Linares, Milton Percy Plasencia; Heimann, Sebastian (Dr.); et al. (Communications Earth & Environment, 2022)
An earthquake swarm affected the Bransfield Strait, Antarctica, a unique rift basin in transition from intra-arc rifting to ocean spreading. The swarm, counting similar to 85,000 volcano-tectonic earthquakes since August 2020, is located close to the Orca submarine volcano, previously considered inactive. Simultaneously, geodetic data reported up to similar to 11 cm north-westward displacement over King George Island. We use a broad variety of geophysical data and methods to reveal the complex migration of seismicity, accompanying the intrusion of 0.26-0.56 km(3) of magma. Strike-slip earthquakes mark the intrusion at depth, while shallower normal faulting the similar to 20 km long lateral growth of a dike. Seismicity abruptly decreased after a Mw 6.0 earthquake, suggesting the magmatic dike lost pressure with the slipping of a large fault. A seafloor eruption is likely, but not confirmed by sea surface temperature anomalies. The unrest documents episodic magmatic intrusion in the Bransfield Strait, providing unique insights into active continental rifting.